Dual site model for the organogenic activity of angiogenin. - Hallahan, T W (1991)
The residues that are indispensable for the ribonucleolytic activity of angiogenin are also known to be essential for its angiogenic activity. We now demonstrate that residues in another region of the protein, devoid of catalytic residues, are additionally required for angiogenesis. Endoproteinase Lys-C or a baby hamster kidney cell protease cleaves angiogenin at the peptide bond either between Lys-60 and Asn-61 or between Glu-67 and Asn-68, respectively. The two polypeptide fragments resulting from either cleavage remain linked by disulfide bonds. These two derivatives and des-(Asn61-Glu67)-angiogenin--in which both bonds are cleaved--retain their ribonucleolytic activities toward tRNA, 18S and 28S rRNA, and dinucleoside phosphates but are no longer angiogenic on the chicken embryo chorioallantoic membrane. Further, their capacity to elicit a second messenger response in endothelial cells is greatly decreased. Moreover, none of these three derivatives inhibit angiogenin-induced angiogenesis. This contrasts with two active site mutants of angiogenin. These results identify the residues from 60 to 68 as a region of angiogenin that is part of a cell-surface receptor binding site [see accompanying manuscript: Hu, G.-F., Chang, S.-I., Riordan, J.F. & Vallee, B.L. (1991) Proc. Natl. Acad. Sci. USA 88, 2227-2231] and serve as the basis for a dual site model of the organogenic activity of angiogenin.